MANAJEMEN PEMBELAJARAN MASA PANDEMI COVID 19 UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR (Studi Kasus Pengelolaan Pembelajaran pada SD Al Falah, SD Al Amin, dan SD Al Husainiyyah Kota Bandung) - Azis Subhan; Ahmad Sanusi; Cahya Syaodih (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The Covid-19 pandemic, is not only a disaster but will be an interesting challenge for educators, especially school teachers. It is interesting to synergize staying still at home while still working. School supervisors, school principals, teachers and students remain healthy but education continues to achieve its goals and visions. If this synergy continues and this pandemic ends, it will produce School Supervisors, Principals, Teachers and New Era Students who are accustomed to the digital era. Learning management in the form of planning, implementation and assessment given by school teachers to students to improve their competence so that they are able to develop their potential so that the teaching profession becomes more qualified, especially after the pandemic is over or if something similar happens in the future that makes the learning process situation not. take place with a face-to-face system at school. The purpose of this study was to obtain data on 1) lesson planning by teachers, 2) implementation of learning by teachers, 3) evaluation / assessment by teachers and 4) barriers, and 5) solutions obtained by teachers in implementing the learning management process reviewed by Principals and supervisors of assisted schools in dealing with these obstacles during the Covid 19 pandemic. By using the case study method, qualitative approach, interview data collection techniques, observation, and documentation study, research subjects for supervisors and teachers in the supervisors of zone A, Coblong district as well as Cidadap, and qualitative analysis, this study shows the results: 1) Learning planning by the teacher, 2) Implementation of learning by the teacher, 3) Evaluation / assessment by the teacher and 4) The obstacles that the teacher gets in carrying out the learning process are studied through constructivism theory from Lev Vygotsky who focuses on students as the subject in learning process by prioritizing social and cultural elements of students can help teachers improve pedagogical competence during the Covid 19 pandemic to better understand the concept of student-centered learning. It is recommended that guidance and training for teachers should continue to be developed in line with the changing times for the sake of improving the quality of Indonesian teachers.